Tradição, modernidade e as bênçãos da Igreja Católica na construção de Goiânia, 1932-1942 - ARAUJO JUNIOR, Edson Domingues de (2011)
This study analyses the coexistence and interaction of modern and traditional symbolic elements within Goiânia's construction and consolidation process, from 1932 to 1942. Focus has been given to the debate regarding contradictions of the discourse of change, based on modernity and on rupture with tradition. To the new political groups in power during the early 1930s, the building of the new capital meant a separation from Goiás State's former days, conceived as decadent and traditional, and the beginning of a political order which placed Goiás on the path to progress and to socio-economic and cultural development. The hypothesis guiding this study seeks to demonstrate that, unlike what the official discourse tended to publicize, Goiânia was built on a dialectics that brought together several symbols and elements from both tradition and modernity. The support offered by the Catholic Church to the government led by Pedro Ludovico Teixeira, concerning the project of building the city and transferring Goiás' administrative headquarters, consists of highly significant evidence not only of the interaction between modern and traditional elements in the construction of Goiânia, but also of the use of traditional symbols as mechanisms that politically legitimise the new political leaders in Goiás.